2020
DOI: 10.1002/jat.4017
|View full text |Cite
|
Sign up to set email alerts
|

Activation of aryl hydrocarbon receptor by benzo[a]pyrene increases interleukin 33 expression and eosinophil infiltration in a mouse model of allergic airway inflammation

Abstract: We recently demonstrated that benzo[a]pyrene (BaP), the aryl hydrocarbon receptor (AhR) ligand, directly contributes to aggravation of cutaneous allergy in a mouse model of allergic dermatitis. The present study aimed to determine whether BaP-induced AhR activation results in development of airway inflammation. Initially, the potential for a direct relationship between BaP-induced AhR activation and airway inflammation was investigated in vivo, using a mouse model of type 2 helper T cell (Th2) hapten toluene-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
2
15
1
Order By: Relevance
“…Furthermore, we found that BaP exposure can activate AhR that subsequently leads to a promotion of Der f 1-induced oxidative stress and IL-25, IL-33, and TSLP release from the epithelium (29). Our findings were supported by some other studies showing that BaP can directly induce AhR activation that contributes to the pro-inflammatory response in respiratory allergy through enhancing IL-33 expression and eosinophil infiltration (17). In the current study, we extended to detect the BaP co-exposure-induced activation of AhR signaling by using AhR reporter plasmid (PGL3-6xDRE-GFP).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, we found that BaP exposure can activate AhR that subsequently leads to a promotion of Der f 1-induced oxidative stress and IL-25, IL-33, and TSLP release from the epithelium (29). Our findings were supported by some other studies showing that BaP can directly induce AhR activation that contributes to the pro-inflammatory response in respiratory allergy through enhancing IL-33 expression and eosinophil infiltration (17). In the current study, we extended to detect the BaP co-exposure-induced activation of AhR signaling by using AhR reporter plasmid (PGL3-6xDRE-GFP).…”
Section: Discussionsupporting
confidence: 87%
“…BaP is one of the ligands to AhR (17). We have previously shown that BaP can induce the expression of AhR and its major downstream gene CYP1A1 in 16HBECs (29).…”
Section: Co-exposure Of Der F 1 With Bap Increases Bap-induced Ahr Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…These data are in agreement with the ability of AhR to bind alarmin promoters and activate their transcription [30]. Interestingly, in vitro co-exposure of human epithelial cell lines to the HDM allergen Dermatophagoides farinae (Der f) and Benzo(a)pyrene (B(a)P), increases the expression of TSLP and IL-33 compared to cells stimulated with one or the other compound, effect also observed in vivo [26,27]. Moreover, Wang et al have shown that pre-incubation of epithelial cells with the AhR inhibitor CH223191 or transfection with a siRNA targeting the AhR decreases the expression of both cytokines, through effects on reactive oxygen species (ROS) production.…”
Section: Ahr Increases Allergic Airway Inflammation By Activating Lung Epithelial Cells and Fibroblastssupporting
confidence: 82%
“…Polycyclic aromatic hydrocarbons (PAHs) represent a dangerous group of chemical mixtures (Błaszczyk & Mielżyńska‐Švach, 2017; Tajima, Tajiki‐Nishino, Watanabe, Kurata, & Fukuyama, 2020). Their genotoxic, mutagenic, carcinogenic, and immunotoxic effects have been described previously (IARC, 2010, 2020).…”
Section: Introductionmentioning
confidence: 99%